Policy Fluctuations and Their Impact on Quality Assurance in Higher Education in Nigeria - ODUKOYA, Adesola Afusat (Jurnal Saintifik (Multi Science Journal), 2025)
Policy fluctuations have remained a critical challenge in managing higher education in Nigeria. This research investigates the impact of policy fluctuations on quality assurance in Nigerian higher education, a pressing issue amid ongoing educational reforms. The study evaluates how varying policy stability affects institutional performance and academic standards. Employing a descriptive survey design, the research involved case studies of five selected Nigerian universities, incorporating qualitative insights from interviews with stakeholders such as administrators, lecturers, and policymakers. Two hundred fifty respondents, including students and academic and non-academic staff, were surveyed using a self-designed questionnaire titled "Policy Fluctuations and Their Impact on Quality Assurance in Higher Education in Nigeria." The questionnaire featured demographic questions and key variables related to planning, management, infrastructure, and educational standards, measured on a four-point Likert scale. Data analysis included simple percentages, frequency counts, and hypothesis testing using the Chi-square (X²) statistical tool at a 0.05 significance level. The findings revealed that policy fluctuations significantly disrupt quality assurance mechanisms and that active stakeholder engagement can mitigate these adverse effects. The research concludes that stable, inclusive policy frameworks are essential for enhancing educational quality. This study contributes to the existing literature by providing empirical evidence on the relationship between policy dynamics and quality assurance, offering practical recommendations for policymakers and educational leaders to foster improved institutional outcomes in the Nigerian higher education landscape.